Gut microbiota and metabolome signatures in obese and normal-weight patients with colorectal tumors - Marta La Vecchia; Michela Giulia Clavenna; Marika Sculco; Gloria Sala; Denise Marradi; Elettra Barberis; Soni Joseph; Marta Mellai; Nico Pagano; Renzo Boldorini; Barbara Azzimonti; Elisa Bona; et al. (iScience)
Summary: Here, we aim to improve our understanding of various colorectal cancer (CRC) risk factors (obesity, unhealthy diet, and gut microbiota/metabolome alteration), analyzing 120 patients with colon polyps, divided in normal-weight (NW) or overweight/obese (OB). Dietary habits data (validated EPIC questionnaires) revealed a higher consumption of processed meat among OB vs. NW patients. Both mucosa-associated microbiota (MAM) on polyps and lumen-associated microbiota (LAM) analyses uncovered distinct bacterial signatures in the two groups. Importantly, we found an enrichment of the pathogenic species Finegoldia magna in MAM of OB patients, regardless of their polyp stage. We observed distinct mucosal-associated metabolome signatures, with OB patients showing increased pyroglutamic acid and reduced niacin levels, and performed microbiota-metabolome integrated analysis. These findings support a model where different risk factors may contribute to tumorigenesis in OB vs. NW patients, highlighting the potential impact of processed meat consumption and F. magna on CRC development among OB patients.